2008
DOI: 10.1164/rccm.200706-958oc
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β Regulates House Dust Mite–induced Allergic Airway Inflammation but Not Airway Remodeling

Abstract: Collectively, these data suggest that TGF-beta regulates HDM-induced chronic airway inflammation but not remodeling, and furthermore, caution against the use of therapeutic strategies aimed at interfering with TGF-beta activity in the treatment of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 58 publications
7
74
0
Order By: Relevance
“…The differential requirements to develop airway remodeling between OVA-and HDM-based models has been extensively discussed by Fattouh and Jordana (29). It has previously been shown using neutralizing antibodies to TGF-b that this cytokine mediates OVA-induced airway remodeling (11); however, remodeling can develop independently of TGF-b after respiratory exposure to HDM extract (30). The data presented in the current study suggest that activin A signaling via Smad2 is responsible for driving airway remodeling after HDM challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The differential requirements to develop airway remodeling between OVA-and HDM-based models has been extensively discussed by Fattouh and Jordana (29). It has previously been shown using neutralizing antibodies to TGF-b that this cytokine mediates OVA-induced airway remodeling (11); however, remodeling can develop independently of TGF-b after respiratory exposure to HDM extract (30). The data presented in the current study suggest that activin A signaling via Smad2 is responsible for driving airway remodeling after HDM challenge.…”
Section: Discussionmentioning
confidence: 99%
“…BAL was performed as previously described (12). Briefly, lungs were dissected and the tracheae were cannulated with a polyethylene tube (outer/inner diameter ϭ 0.965/0.58 mm; BD Biosciences).…”
Section: Collection and Measurement Of Specimensmentioning
confidence: 99%
“…Levels of IL-5, IL-4, IL-13, and IFN-␥ in supernatants from mononuclear cell cultures were measured by DuoSet ELISA kits purchased from R&D Systems and used according to the manufacturer's instruction. Levels of HDMspecific IgE, IgG1, and IgG2 were measured by sandwich ELISA as previously described (2,12).…”
Section: Cytokine Analysis and Ig Measurementsmentioning
confidence: 99%
“…TGF-β-producing T cells can suppress airway inflammation and hyperresponsiveness induced by Th2 effector cells in a murine allergic airway model [17,18]. However, it was recently shown that TGF-β/Smad2 signaling proteins were expressed in the majority of cells infiltrating into the airway in mouse models [19-22] and human asthma [19,23]. …”
Section: Introductionmentioning
confidence: 99%